THE EFFECTIVENESS OF PROJECT BASED LEARNING AND PROBLEM BASED LEARNING FOR TEACHING BIOGRAPHY TEXT WRITING TO HIGHLY AND LOWLY MOTIVATED STUDENTS - Wachyu, Meike Imeda; Rukmini, Dwi (Language Circle: Journal of Language and Literature, 2015)
The aims of this study were (1) to find out the effectiveness of using project based learning compared to problem based learning to teach writing biography texts to highly motivated students, (2) to find out the effectiveness of using project based learning compare to problem based learning to teach writing biography texts to lowly motivated students, (3) to find out the effectivenessin teaching writing biography texts through control group to highly motivated students,(4) to find out the effectivenessin teaching writing biography texts through control group to lowly motivated students.(5)to explain the significant difference between students high motivation in writing competence and students low motivation in writing competence taught using project based learning compared to problem based learning (6) to explain the interaction between learning models, studentsâ motivation, and writing biography texts.